Does corporate integrity affect firm efficiency? - Giang Thi Minh Vu; Minh-Huyen Dao; Khanh Hoang (Borsa İstanbul Review, 2025)
This study investigates how corporate integrity influenced firm efficiency in the United States in 2001-2018. Based on a measure of corporate integrity computed by machine learning and a measure of firm efficiency generated by data envelopment analysis, the results of our multivariate regression suggest that greater corporate integrity is generally associated with higher firm efficiency. This finding indicates that in a more integral culture, firms can optimize the use of resources to generate revenues more efficiently. We identify corporate social responsibility engagement as a channel through which integrity positively impacts firm efficiency. Interestingly, hiring external CEOs does not seem to result in a significant change in firm efficiency in terms of corporate integrity, suggesting that importing culture into top management does not change the effect of corporate integrity on firm efficiency.
Keywords: 330